Effects of geometrical configurations on melting and solidification processes in phase change materials - Kiyak, Burak; Öztop, Hakan Fehmi; Biswas, Nirmalendu; Selimefendigil, Fatih (Pergamon-Elsevier Science Ltd, 2025)
Phase-change materials (PCMs) are recognized for their effective role in thermal energy storage systems, offering the potential to balance fluctuations between energy supply and demand by absorbing, storing, and releasing heat during phase transitions. The performance of such systems, however, is heavily influenced by the melting and solidification behaviors of the PCM, which depend on the system's geometric configuration and heat source placement. In this research, a comprehensive numerical analysis is conducted to examine the thermal behavior of a PCM-filled energy storage unit, with particular focus on the effects of heater and cooler positioning (bottom, side, and top) and the influence of two distinct geometrical shapes (square and circular). A finite volume-based computational technique is employed to solve the governing equations, and the numerical outcomes are validated against experimental data from in-house tests. The investigation covers both the melting and solidification stages for two geometries under different Grashof numbers (Gr), which quantify the strength of natural convection within the system. The results reveal that heating from the side offers the quickest melting performance, especially for the circular configuration at lower Gr values, where a melting rate 240% higher than bottom heating is observed. On the other hand, top heating proves to be the least efficient. For solidification, the best performance is obtained using a square geometry with a top cooling configuration, resulting in a solidification rate 15.4% faster than the bottom cooling scenario. This study highlights the critical role of geometric shape and heater/cooler positioning in enhancing the thermal response of PCM systems. The findings suggest that side heating combined with circular geometries is optimal for accelerating the melting process, while square geometries with top cooling enhance the solidification rate. Future research areas include exploring more complex geometries, varied boundary conditions, and different PCM materials with distinct thermal characteristics.
Keywords: Phase change material (PCM); Melting; Solidification; Cooler shape and position; Energy storage; Experimental